SYSTEMATIC LITERATURE REVIEW ANALYSIS OF POSITIVE E-WOM ON THE TOURIST FUTURE BEHAVIOR IN TOURISM VILLAGE MARKETING - Juliana, Juliana; Sihombing, Sabrina O; Antonio, Ferdi (Jurnal Ilmiah Global Education, 2023)
This article provides an in-depth, systematic literature review on the positive impact of e-WOM in the tourism village marketing context. The purpose of this study is to determine the research gap, trend or impact pattern of positive e-wom from the research keyword, namely Positive E- Wom using the Publish or Perish application as a search for the Research Journal database and Vos Viewer as a graphical visualization for determining research gaps. Through systematic literature research methodology, filtered and analyzed various relevant articles from various databases. The results illustrate the various positive impacts of e-WOM. Based on the curated results of research sources, only 100 articles were relevant to the 2018-2023 research time interval from several databases. Based on the research gap analysis using the Mendeley Application and Vos Viewer, the keywords that are relevant to Positive E-Wom research are obtained, namely tourist destination, destination image, intention, positive impact, tourism, Social Medium, Tourist Satisfaction, decision and which has the lowest Research Gap or Variables rarely studied which affect positive E-wom are tourist destination, intention, negative impact/anxiety, enjoyment, esthetic, escapism, authenticity and memorable tourism experience, social media context, symbolic value, tourist delight which are variables that are not visible in the VOS viewer visualization. In this context, positive e-WOM also has a viral effect that is able to reach a wide audience in a short time, as well as encourage active tourist participation in providing feedback and reviews.